Preparation of halide sensors by means of co-precipitation of silver sulphide and silver halide - Rajbhandari, Armila; Manandhar, Krishna; Pradhananga, Raja Ram (Journal of Nepal Chemical Society, 2013)
Halide sensors have been prepared in the laboratory by means of co-precipitation of silver sulphide and silver halide and is used for the determination of iodide, bromide and chlorides ions. The iodide sensors show a Nernstian response in the concentration range of 10-1 to 10-6M iodide ions, bromide sensors show a linear response in the concentration range of 10-1 to 10-5M bromide ions while chloride sensors show linear response upto the concentration range of 10-4M chloride ions. The response time of all the electrodes, is < 1minute. The iodide sensors were found to be selective towards iodide ions in the presence of Cl- and Br- ions while bromide and chloride sensors interferred by iodide ions as indicated by selectivity coefficient values of 3.98 and 48.9 respectively. These sensors have been successfully applied for potentiometric titrations.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9390Journal of Nepal Chemical Society Vol. 30, 2012 Page:  168-173 Uploaded date: 12/20/2013